2002
DOI: 10.1007/s10123-002-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of vancomycin-resistant enterococci in clinical samples from hospitalized patients of the Canary Islands, Spain

Abstract: Over the last decade vancomycin-resistant enterococci (VRE) have emerged as nosocomial pathogens. The aim of this study was to determine the prevalence of VRE in clinical samples from hospitalized patients in the Canary Islands. From April to November 2000, 437 enterococci were isolated from patients hospitalized at the four main health care centers in those islands. Identification to the species level was performed with the GPS-TA (Vitek 1) or the Wider I system. A PCR assay was used to determine the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
4
2
Order By: Relevance
“…Our finding was higher than the prevalence reported in the studies from Spain (0.7%), 24 France (1.0%), 25 Europe (4.0%) 26 and Canada (6.0%) 27 whereas lower than that of the United States (35.5%) 28 . North America (21%), 23 Belgium (12.8%), 29 Germany (9.8%) and 30 the United Kingdom (9.2%) 31 .…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our finding was higher than the prevalence reported in the studies from Spain (0.7%), 24 France (1.0%), 25 Europe (4.0%) 26 and Canada (6.0%) 27 whereas lower than that of the United States (35.5%) 28 . North America (21%), 23 Belgium (12.8%), 29 Germany (9.8%) and 30 the United Kingdom (9.2%) 31 .…”
Section: Discussioncontrasting
confidence: 86%
“…It is closer to the prevalence of 11.9%, reported by a surveillance study among 4018 Enterococci species in the Asia Pacific region and lower than the reported prevalence of 23% by a meta-analysis among the patients with malignancy in Asia. 22,23 Our finding was higher than the prevalence reported in the studies from Spain (0.7%), 24 France (1.0%), 25 Europe (4.0%) 26 and Canada (6.0%) 27 whereas lower than that of the United States (35.5%). 28 North America (21%), 23 Belgium (12.8%), 29 Germany (9.8%) and 30 the United Kingdom (9.2%).…”
Section: Discussioncontrasting
confidence: 72%
“…The phenotypic methods such as E-test are the convenient and useful meth-ods for determining of MIC values for vancomycin in enterococci. Our result are in accordance with the other studies which conducted by Sharifi et al in Iran, but, in contrast to the results of the study which performed by Pérez-Hernández et al 13,17 Horizontal gene transfer has an important role for the dissemination of resistance genes in enterococci and transposon (Tn1546) also has an important role for the dissemination of vancomycin resistance genes. Although primarily vanA cluster (Tn1546 and Tn5482) was identified in E. faecium, it has also been detected in E. faecalis.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported a lower prevalence, eg, in Spain only three cases were resistant to vancomycin from 437 Enterococcus samples. 54 A prevalence of 6.7% was reported in a study in Canada, 55 9% in a study in New York, 56 and 2%–9% in a separate study in the USA. 57 60 In soEurope, a prevalence of 1% in France and 59% in Portugal was reported.…”
Section: Discussionmentioning
confidence: 94%